A circular economy study on the characterization and thermal properties of thermoplastic composite created using regenerated carbon fiber recycled from waste thermoset CFRP bicycle part as reinforcement. (10th November 2022) - Chen, Cheng-Ho; Chiang, Chin-Lung; Wang, Jia-Xun; Shen, Ming-Yuan
Abstract: Thermoset composite mean fiber reinforced thermoset plastic, especially using carbon fiber (CF) as the reinforcement. Nowadays, carbon fiber reinforced thermoset plastic (CFRP) waste is the biggest problem that hinders the application and development of composites. In view of the increasingly stringent environmental regulations regarding disposal of the composites, it is necessary to attach great importance to composite waste recycling and to research to enhance the development of the composite industry. Two types of regenerated carbon fiber were used in this study. A novel microwave‐assisted pyrolysis (MAP) recycle technology was used to remove the resin in the waste CFRP bicycle parts and successfully recover the recycled carbon fiber (rCF). To evaluate the characteristics of this recycled carbon fiber, another woven off-cut carbon fiber (oCF), recycled without any chemical or thermal energy, was used. This study also used these two regenerated carbon fibers as reinforcements to prepare the thermoplastic composite (CFRTP) and investigate its thermal properties. The experimental results show that rCF can be obtained with precisely controlled microwave conditions so that the resin in the CFRP waste can be almost completely pyrolyzed without damaging the fiber structure, and the sizing on the fiber surface can also be pyrolyzed. The experimental results also show that the thermal properties of CFRTP reinforced with rCF are better than those of the thermoplastic composite reinforced with oCF. Graphical abstract: Image 1